Unveiling the metabolic roles: how lead exposure elevates uric acid levels - Wanlu Liu; Yaotang Deng; Guoliang Li; Zhiqiang Zhao; Xinyu Zhu; Jiazhen Zhou; Mushi Yi; Simin Xian; Yue Hu; Youyi Wu; Qiaoyuan Yang; Lili Liu; et al. (Environmental Sciences Europe)
Abstract Chronic lead (Pb) exposure remains a global public health concern throughout the world. Particularly the populations in industrial or polluted environments tend to have an increased risk of metabolic imbalance in uric acid (UA). However, the metabolic profile alteration under Pb exposure-induced UA elevation is largely unknown. This study included 505 participants occupationally exposed to Pb, and levels of blood Pb, UA, and estimated glomerular filtration rate (eGFR) were assessed. Untargeted metabolomics was used to profile serum metabolome among a representative sample of 90 workers. To elucidate the effects of Pb exposure on UA level and metabolic alterations, as well as to investigate the mediating roles of metabolites and eGFR, generalized additive models alongside parallel and serial mediation analyses were employed. We found that blood Pb levels were related to high UA levels and low eGFR, respectively. The 10 Pb exposure-related metabolites were mainly enriched in amino acid metabolism and lipid metabolism, and this metabolite mixture as a whole (present as a weighted quantile sum index) had positive and negative dose–response relationships with UA [β (95%CI) = 0.49 (0.28, 0.70), P < 0.001] and eGFR [β (95%CI) = − 2.54 (− 2.30, − 2.78), P < 0.001], respectively. Metabolites and eGFR played no parallel mediation roles but played serial mediating effects on Pb exposure-UA associations (Pb → wqs index → eGFR → UA, mediation proportion = 40.7%). In particular, a significant indirect path involving mediators in a causal chain of 3-Methoxytyrosine to eGFR (Pb → 3-Methoxytyrosine → eGFR → UA, mediation proportion = 22.0%) was observed. Our findings reveal a causal chain, metabolic alteration, and subsequent kidney function decline involved in the physiologies and pathogenesis of Pb exposure-induced UA elevation, indicating several key metabolites could serve as a target for effective prevention and treatment.